RT-PCR TEST FOR DETECTION OF DENGUE VIRUS-3 IN INTRATHORACALLY INFECTED Aedes aegypti - Asyhar Tunissea; Dyah Widiastuti; Nastiti Wijayanti (Pusbindiklat - LIPI, 2012)
Dengue viruses, globally the most prevalent arboviruses, are transmitted to humans by persistently infected Aedes aegypty. Detection of Dengue viral RNA in mosquito thorax using Reverse Transcription Polymerase Chain Reaction (RT-PCR) assay is an alternatives method for Dengue vector surveillance. The study aimed to test RT-PCR technique to detection Dengue-3 in intrathoracally infected Ae. aegypti. The study design was experimental with descriptive analytic using mosquitoes of Dengue Virus-3 were used as infectious samples and non-infected adult Ae. aegypti mosquitoes were used as normal ones. The results shows the RT-PCR technique can detect Dengue-3 viral RNA in intrathoracally Ae. aegypti at 5th ,6th and 7th days incubation.